Intractable Diarrhea in a Newborn Infant: Microvillous Inclusion Disease - Wendy Wilson; R Brent Scott; Alfredo Pinto; Marli A Robertson (Canadian Journal of Gastroenterology)
A newborn male presented with watery diarrhea, dehydration and metabolic acidosis. Severe secretory diarrhea of variable magnitude persisted when the patient was on parenteral nutrition with no oral intake. Initial light microscopic evaluation of a small intestinal mucosal biopsy showed partial villous atrophy and crypt hypoplasia. Ultrastructural studies of the villous enterocyte revealed internalized inclusions of microvilli, typical of microvillous inclusion disease. Presented are a case report and a discussion of the differential diagnosis of watery diarrhea in the neonate, as well as a short review of microvillous inclusion disease.